Model Pembelajaran Team Assisted Individualization dalam Keterampilan Menulis Bahasa Jerman - Andi Nurul Fhadillah Ainun Afidah; Misnah Mannahali; Abd Kasim Achmad (Phonologie : Journal of Language and Literature, 2023)
Abstract. The purpose of this study was to determine the improvement in writing skills of German language texts for class XI students of SMAN 3 Makassar through the application of the Team Assisted Individualization model. This type of research is classroom action research which consists of two cycles with each cycle consisting of two meetings. The subject of this research is class XI MIPA 3 SMAN 3 Makassar. There are two types of research data, namely qualitative data and quantitative data. Qualitative data were obtained from teacher and student observation data, while quantitative data were obtained from students' writing tests. The results of students' text writing tests in cycle 1 obtained an average of 3 and experienced an increase in cycle II with an average value of 5. The results of this study indicate that the application of the Team Assisted Individualization model can improve the German writing skills of class XI students of SMAN 3 Makassar.Keyword: Implementation, Writing, Team Assisted Individualization model